Integrasi Intelijen Ekonomi dalam Tata Kelola Pemerintahan Daerah: Urgensi, Tantangan, & Strategi Penguatannya - Saksono, Herie (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2025)
This study examines the urgency of integrating economic intelligence into regional governance as a single entity within the domestic governance system. The main problem is the suboptimal function of economic intelligence within the Directorate General of Politics and Public Administration of the Ministry of Home Affairs of the Republic Indonesia’s structure and its operationalization by the Regional Government’s Kesbangpol Agency, which has implications for the performance of economic, social, and cultural resilience. This study aims to develop an adaptive economic intelligence integration model, analyze the impacts of this suboptimal function, and formulate strategies for strengthening institutional capacity. Using a qualitative-exploratory approach, data were collected through documentation studies, in-depth interviews with policy actors, and field observations, then analyzed using thematic analysis techniques. This study found obstacles to the transformation of economic intelligence, requiring systemic integration. The gap in human resource capacity also influences the process of technology adaptation and digitalization, and the need for regulations, including their synchronization and harmonization. In the context of strengthening institutional capacity, it is necessary to develop human resources with analytical competence, modernize digital infrastructure, and strengthen cross-institutional networks. Effective implementation of economic intelligence contributes significantly to evidence-based decision-making, regional economic resilience, and the institutional credibility of the Government and Regional Governments. The novelty of this study lies in the adaptive integration model of the Indonesian context, where multi-level government coordination mechanisms are more precise when accompanied by the implementation of competitive strategies in strengthening integrated institutional capacity from the Central-Regional Government. The study concludes that the successful implementation of economic intelligence is highly dependent on vertical-horizontal integration within the government structure. Therefore, it is recommended to formalize the Central-Regional economic intelligence function through the Kesbangpol Agency, develop an integrated information system, develop a sustainable human resource development program, institutionalize the Central-Regional Economic Intelligence Coordination Forum, and implement a performance-based monitoring system.